Wave transformation from statistically rough surface - Bass, F.G.; Vatova, L.B. (Радіофізика та електроніка, 2009)
The generalized small perturbation method is applied to investigate the transformation of waves on statistically rough surface separating media in which several types of waves caused by a time and spatial dispersion propagate. The field boundary conditions have been formulated. The mean intensity of the transformed fields have been calculated Обобщенный метод малых возмущений использован для исследования трансформации волн на статистически шероховатой поверхности, разделяющей среды, в которых изза наличия временной и пространственной дисперсий распространяются несколько типов волн. Сформулированы для поля граничные условия. Рассчитана средняя интенсивность трансформированных волн. Узагальнений метод малих збурень використано для дослідження трансформації хвиль на статистично шорсткій поверхні, що розділяє середовища, в яких із-за наявності часової та просторової дисперсій розповсюджуються декілька типів хвиль. Сформульовано для поля граничні умови. Розраховано середню інтенсивність трансформованих хвиль.